High-strength cold-resistant fiber and preparation method thereof
Through electrospinning technology of modified graphene oxide and premodified polyacrylate emulsion, high-strength cold-resistant fibers were prepared by combining silicon-phosphorus-nickel complexes and zinc ions, which solved the static electricity, warmth and temperature of the fibers in winter clothing. The flame retardant problem achieves efficient flame retardant, thermal conductivity and antistatic properties, and enhances anti-aging and antibacterial capabilities.
Patent Information
- Application Number
- CN202411625720.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing fibers lack good anti-static, warm and flame retardant properties in winter clothing, resulting in static accumulation and heat loss problems.
Modified graphene oxide, 2,5-dihydroxyterephthaldehyde and premodified polyacrylate emulsion were prepared by electrospinning technology, combining silicon phosphorus-nickel complexes and zinc ions to form flame retardant , thermally conductive and antistatic fiber structure.
It improves the flame retardant ability, warmth and anti-static properties of the fiber, enhances the mechanical properties and anti-aging capabilities of the material, and also has good antibacterial properties.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of fibers, in particular to a high-strength cold-resistant fiber and a preparation method thereof. Background Art
[0002] Polyacrylate fiber is a synthetic fiber material with excellent properties. It has good wrinkle resistance, abrasion resistance and light resistance, and is widely used in the manufacture of textiles. Polyacrylate fiber can be made into various clothing, household items and industrial textiles, such as clothing, bedding, curtains, etc. These textiles are soft, comfortable, easy to clean and durable, and are favored by consumers.
[0003] Keeping warm is an essential attribute of winter clothing. Winter weather is relatively dry, and the insulation resistance between objects is large. Most fibers, especially chemical fibers, are poor conductors and insulators. When people are active, friction between these clothes and between the human body occurs, generating static electricity that accumulates on the fibers of the clothes. When a certain voltage intensity is reached, static electricity is generated, causing harm to the human body. Therefore, this article introduces a cold-resistant fiber with anti-static ability. Summary of the invention
[0004] The purpose of the present invention is to provide a high-strength cold-resistant fiber and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] A high-strength cold-resistant fiber, which is obtained by electrostatic spinning after the reaction of modified graphene oxide, 2,5-dihydroxyterephthalaldehyde and pre-modified polyacrylate emulsion; The modified graphene oxide is prepared by batch reaction of graphene oxide and 1-aminopyrrole; The pre-modified polyacrylate emulsion is prepared by reacting an olefin mixed solution, azobisisobutyronitrile, a hydrochloric acid solution and a silicon mixed solution, diluting the mixture with 4-methylcyclohexanone, and then reacting the mixture with zinc bromide.
[0006] A method for preparing high-strength cold-resistant fiber, characterized in that the method for preparing high-strength cold-resistant fiber mainly comprises the following preparation steps: (1) In an air atmosphere, diphenylphosphine and triallylmethoxysilane are uniformly mixed in a molar ratio of 3:1, placed in a high-pressure reactor, and reacted at 115-125°C for 10-12 hours to obtain phosphorus-containing siloxane; at 200-300 r / min, under nitrogen protection, the phosphorus-containing siloxane solution is uniformly added to a nickel bromide solution of equal mass to the phosphorus-containing siloxane solution within 10-18 minutes, and the stirring is continued for 22-26 hours, and the mixture is dried at 40-50°C for 22-24 hours to obtain a silicon-phosphorus-nickel complex; (2) Take 6-8 parts of 4-methylcyclohexanone, 3-5 parts of olefin mixture, 0.03-0.05 parts of azobisisobutyronitrile, 2-3 parts of 6-8% hydrochloric acid solution and 0.8-1 parts of silicon mixture by mass, heat 4-methylcyclohexanone to 140-144°C, add olefin mixture, azobisisobutyronitrile, hydrochloric acid solution and silicon mixture at a uniform rate within 1-2 hours, heat to 145-155°C, continue reaction for 70-90 minutes, and then reduce to room temperature. The mixture was heated to room temperature, and the pH was adjusted to 6.5-7.5 with dimethylethanolamine to obtain a polyacrylate emulsion; the polyacrylate emulsion, sodium sulfide and deionized water were mixed in a mass ratio of 1:0.3-0.5:1, and stirred at 200-300 r / min for 2-3 min, a 4-methylcyclohexanone layer was taken, and zinc bromide in an amount of 0.08-0.1 times the mass of the polyacrylate emulsion was added, and stirred at 200-300 r / min for 2-4 h to obtain a pre-modified polyacrylate emulsion; (3) Mix graphene oxide and deionized water in a mass ratio of 1:80~100, ultrasonicate for 50~70min, add a carboxyl activator of the same mass as graphene oxide, activate for 25~35min, take out, add 1-aminopyrrole of the same mass as graphene oxide at a uniform speed within 8~10min at 50~70℃ and 200~300r / min, continue stirring for 80~100min, immerse in ethanol and let stand for 50~70min, centrifuge, wash with ethanol 3~5 times, and vacuum dry at -10~0℃ for 22~26h to obtain pre-modified graphene oxide; mix pre-modified graphene oxide, 1-aminopyrrole, ethanol and deionized water in a mass ratio of 1:3~5:1~3:7~9, stir at 200~300r / min for 8~10min, filter, and dry at 40~60℃ for 22~26h to obtain modified graphene oxide; (4) The modified graphene oxide, 2,5-dihydroxyterephthalaldehyde, pre-modified polyacrylate emulsion and ethanol are uniformly mixed in a molar ratio of 1:0.8-0.9:10-12:6-8 to obtain a modified polyacrylate emulsion; the modified polyacrylate emulsion is electrospun, allowed to stand for 6-8 hours, and naturally cooled to room temperature to obtain modified polyacrylate fibers.
[0007] As an optimization, the phosphorus-containing siloxane solution in step (1) is prepared by uniformly mixing phosphorus-containing siloxane and dichloromethane in a mass ratio of 1:4-5.
[0008] As an optimization, the nickel bromide solution in step (1) is prepared by uniformly mixing nickel bromide and dichloromethane in a mass ratio of 1:8-10.
[0009] As an optimization, the olefin mixture in step (2) is prepared by uniformly mixing methyl methacrylate, isooctyl acrylate, butyl acrylate, allyltrimethoxysilane and acrylamine in a mass ratio of 1:1:1:0.3~0.5:0.3~0.5.
[0010] As an optimization, the silicon mixed liquid in step (2) is prepared by uniformly mixing dimethyldimethoxysilane and silicon-phosphorus-nickel complex in a mass ratio of 1:0.2-0.4.
[0011] As an optimization, the carboxyl activator in step (3) is prepared by mixing 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide in a mass ratio of 1:1.
[0012] As an optimization, the electrospinning parameters of step (4) are as follows: liquid flow rate of 0.18-0.22 ml / h, receiving distance of 14-16 cm, and spinning voltage of 16-18 KV.
[0013] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing the high-strength cold-resistant fiber, the present invention sequentially reacts diphenylphosphine with triallylmethoxysilane and nickel bromide to obtain a silicon-phosphorus-nickel complex; reacts an olefin mixed solution, azobisisobutyronitrile, a hydrochloric acid solution and a silicon mixed solution, dilutes the solution with 4-methylcyclohexanone and reacts the solution with zinc bromide to obtain a pre-modified polyacrylate emulsion; reacts graphene oxide with 1-aminopyrrole in batches to obtain modified graphene oxide; and electrostatically spins the modified graphene oxide, 2,5-dihydroxyterephthalaldehyde and the pre-modified polyacrylate emulsion to obtain the high-strength cold-resistant fiber.
[0014] First, diphenylphosphine is reacted with triallylmethoxysilane and nickel bromide in sequence to obtain a silicon-phosphorus-nickel complex; the organic phosphorus in the silicon-phosphorus-nickel complex can react chemically with active free radicals generated during the combustion process, thereby inhibiting the generation and conduction of free radicals and preventing effective contact between oxygen and the combustion material, which can reduce the activity of the surface of the combustion material, slow down the formation of flames and the rate of the combustion reaction, thereby playing a flame retardant role; at the same time, the organic phosphorus can also release a large amount of phosphorus-containing compounds during the combustion process, and these compounds can generate phosphates with carbon on the surface of the combustion material at high temperature to form a phosphate protective layer, which covers the surface of the combustion material and plays a role of heat insulation and oxygen isolation, preventing the combustion material from continuing to burn, thereby improving the flame retardant ability of the material, and the silicon-phosphorus-nickel complex can also catalyze the polymerization of acrylates and accelerate the reaction process.
[0015] Secondly, the olefin mixture, azobisisobutyronitrile, hydrochloric acid solution and silicon mixture are reacted and diluted with 4-methylcyclohexanone and then reacted with zinc bromide to obtain a pre-modified polyacrylate emulsion; when the long silicon-oxygen chain burns, the silicon-oxygen bond in the molecule will be converted into a silicon-carbon bond, and together with the generated carbonized product, a composite carbon layer is formed. This composite carbon layer has the advantages of blocking heat, isolating oxygen, and preventing molten droplets, which seals the polymer material and prevents the flammable gas from diffusing outward, thereby improving the flame retardant ability of the material; reacting with zinc bromide to introduce zinc ions, which can destroy its biofilm and metabolic basis, and can also affect the DNA replication and transcription of bacteria, hinder its growth and reproduction, and achieve the effect of inhibiting and killing bacteria.
[0016] Finally, graphene oxide and 1-aminopyrrole are reacted in batches to obtain modified graphene oxide; modified graphene oxide, 2,5-dihydroxyterephthalaldehyde, and pre-modified polyacrylate emulsion are reacted and then electrostatically spun to obtain high-strength cold-resistant fibers. Graphene oxide has good thermal conductivity and can effectively conduct the heat generated by the human body to various parts of the fiber, maintain uniform distribution of body temperature, improve the warming effect, and effectively prevent the invasion of external cold air, reduce heat loss, and thus enhance the warming effect of the material; polypyrrole is prepared on the surface of graphene oxide. As a conductive polymer, it can absorb and disperse static charge, thereby reducing the accumulation of static electricity and reducing the surface resistivity of the material; the surfaces of modified graphene oxide and pre-modified polyacrylate emulsion are rich in amino groups, which can react with the aldehyde group of 2,5-dihydroxyterephthalaldehyde and form a structure that can absorb ultraviolet light with the hydroxyl group on 2,5-dihydroxyterephthalaldehyde, thereby achieving an anti-aging effect, and can also convert the absorbed ultraviolet light into thermal energy, thereby enhancing the warming performance of the material. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0018] Example 1
[0019] A method for preparing high-strength cold-resistant fiber mainly comprises the following preparation steps: (1) In an air atmosphere, diphenylphosphine and triallylmethoxysilane were mixed uniformly in a molar ratio of 3:1, placed in a high-pressure reactor, and reacted at 115°C for 10 hours to obtain phosphorus-containing siloxane; at 200 r / min, under nitrogen protection, the phosphorus-containing siloxane solution was uniformly added to a nickel bromide solution of equal mass to the phosphorus-containing siloxane solution within 10 minutes, and the mixture was stirred for 22 hours, and dried at 40°C for 22 hours to obtain a silicon-phosphorus-nickel complex; (2) Take 6 parts of 4-methylcyclohexanone, 3 parts of olefin mixture, 0.03 parts of azobisisobutyronitrile, 2 parts of 6% hydrochloric acid solution and 0.8 parts of silicon mixture by mass, heat 4-methylcyclohexanone to 140°C, add olefin mixture, azobisisobutyronitrile, hydrochloric acid solution and silicon mixture at a uniform rate within 1 hour, heat to 145°C, continue to react for 70 minutes, then cool to room temperature, adjust pH to 6.5 with dimethylethanolamine, and prepare polyacrylate emulsion; mix polyacrylate emulsion, sodium sulfide and deionized water in a mass ratio of 1:0.3:1, stir at 200 r / min for 2 minutes, take the 4-methylcyclohexanone layer, add zinc bromide in an amount of 0.08 times the mass of polyacrylate emulsion, and stir at 200 r / min for 2 hours to prepare pre-modified polyacrylate emulsion; (3) Graphene oxide and deionized water were mixed in a mass ratio of 1:80, ultrasonicated for 50 minutes, a carboxyl activator of the same mass as the graphene oxide was added, activated for 25 minutes, taken out, and 1-aminopyrrole of the same mass as the graphene oxide was added at a uniform speed within 8 minutes at 50°C and 200 r / min, and stirring was continued for 80 minutes. The mixture was immersed in ethanol and allowed to stand for 50 minutes, centrifuged, washed with ethanol three times, and vacuum dried at -10°C for 22 hours to obtain pre-modified graphene oxide; pre-modified graphene oxide, 1-aminopyrrole, ethanol and deionized water were mixed in a mass ratio of 1:3:1:7, stirred at 200 r / min for 8 minutes, filtered, and dried at 40°C for 22 hours to obtain modified graphene oxide; (4) The modified graphene oxide, 2,5-dihydroxyterephthalaldehyde, pre-modified polyacrylate emulsion and ethanol were uniformly mixed in a molar ratio of 1:0.8:10:6 to obtain a modified polyacrylate emulsion; the modified polyacrylate emulsion was electrospun, allowed to stand for 6 hours, and naturally cooled to room temperature to obtain modified polyacrylate fibers.
[0020] Example 2 A method for preparing high-strength cold-resistant fiber mainly comprises the following preparation steps: (1) In an air atmosphere, diphenylphosphine and triallylmethoxysilane were uniformly mixed in a molar ratio of 3:1, placed in a high-pressure reactor, and reacted at 120°C for 11 hours to obtain phosphorus-containing siloxane; at 250 r / min, under nitrogen protection, the phosphorus-containing siloxane solution was uniformly added to a nickel bromide solution of equal mass to the phosphorus-containing siloxane solution within 14 minutes, and the mixture was stirred for 24 hours, and dried at 45°C for 23 hours to obtain a silicon-phosphorus-nickel complex; (2) Take 7 parts of 4-methylcyclohexanone, 4 parts of olefin mixture, 0.04 parts of azobisisobutyronitrile, 2.5 parts of 7% hydrochloric acid solution and 0.9 parts of silicon mixture by mass, heat 4-methylcyclohexanone to 142°C, add olefin mixture, azobisisobutyronitrile, hydrochloric acid solution and silicon mixture at a uniform rate within 1.5 hours, heat to 150°C, continue to react for 80 minutes, then cool to room temperature, adjust pH to 7 with dimethylethanolamine, and prepare polyacrylate emulsion; mix polyacrylate emulsion, sodium sulfide and deionized water in a mass ratio of 1:0.4:1, stir at 250 r / min for 2.5 minutes, take the 4-methylcyclohexanone layer, add zinc bromide (0.09 times the mass of polyacrylate emulsion), stir at 250 r / min for 3 hours, and prepare pre-modified polyacrylate emulsion; (3) Graphene oxide and deionized water were mixed in a mass ratio of 1:90, ultrasonicated for 60 minutes, a carboxyl activator of the same mass as the graphene oxide was added, activated for 30 minutes, taken out, and 1-aminopyrrole of the same mass as the graphene oxide was added at a uniform speed within 9 minutes at 60°C and 250 r / min, and stirring was continued for 90 minutes. The mixture was immersed in ethanol and allowed to stand for 60 minutes, centrifuged, washed with ethanol 4 times, and vacuum dried at -5°C for 24 hours to obtain pre-modified graphene oxide; pre-modified graphene oxide, 1-aminopyrrole, ethanol and deionized water were mixed in a mass ratio of 1:4:2:8, stirred at 250 r / min for 9 minutes, filtered, and dried at 50°C for 24 hours to obtain modified graphene oxide; (4) The modified graphene oxide, 2,5-dihydroxyterephthalaldehyde, pre-modified polyacrylate emulsion and ethanol were uniformly mixed in a molar ratio of 1:0.85:11:7 to obtain a modified polyacrylate emulsion; the modified polyacrylate emulsion was electrospun, allowed to stand for 7 hours, and naturally cooled to room temperature to obtain modified polyacrylate fibers.
[0021] Example 3
[0022] A method for preparing high-strength cold-resistant fiber mainly comprises the following preparation steps: (1) In an air atmosphere, diphenylphosphine and triallylmethoxysilane were mixed uniformly in a molar ratio of 3:1, placed in a high-pressure reactor, and reacted at 125°C for 12 hours to obtain phosphorus-containing siloxane; at 300 r / min, under nitrogen protection, the phosphorus-containing siloxane solution was uniformly added to a nickel bromide solution of equal mass to the phosphorus-containing siloxane solution within 18 minutes, and the mixture was stirred for 26 hours, and dried at 50°C for 24 hours to obtain a silicon-phosphorus-nickel complex; (2) Take 8 parts of 4-methylcyclohexanone, 5 parts of olefin mixture, 0.05 parts of azobisisobutyronitrile, 3 parts of 8% hydrochloric acid solution and 1 part of silicon mixture by mass, heat 4-methylcyclohexanone to 144°C, add olefin mixture, azobisisobutyronitrile, hydrochloric acid solution and silicon mixture at a uniform rate within 2 hours, heat to 155°C, continue to react for 90 minutes, then cool to room temperature, adjust pH to 7.5 with dimethylethanolamine, and prepare polyacrylate emulsion; mix polyacrylate emulsion, sodium sulfide and deionized water in a mass ratio of 1:0.5:1, stir at 300 r / min for 3 minutes, take the 4-methylcyclohexanone layer, add zinc bromide 0.1 times the mass of polyacrylate emulsion, stir at 300 r / min for 4 hours, and prepare pre-modified polyacrylate emulsion; (3) Graphene oxide and deionized water were mixed in a mass ratio of 1:100, ultrasonicated for 70 minutes, a carboxyl activator of the same mass as the graphene oxide was added, activated for 35 minutes, taken out, and 1-aminopyrrole of the same mass as the graphene oxide was added at a uniform rate within 10 minutes at 70°C and 300 r / min, and the stirring was continued for 100 minutes. The mixture was immersed in ethanol and allowed to stand for 70 minutes, centrifuged, washed with ethanol for 5 times, and vacuum dried at 0°C for 26 hours to obtain pre-modified graphene oxide; the pre-modified graphene oxide, 1-aminopyrrole, ethanol and deionized water were mixed in a mass ratio of 1:5:3:9, stirred at 300 r / min for 10 minutes, filtered, and dried at 60°C for 26 hours to obtain modified graphene oxide; (4) The modified graphene oxide, 2,5-dihydroxyterephthalaldehyde, pre-modified polyacrylate emulsion and ethanol were uniformly mixed in a molar ratio of 1:0.9:12:8 to obtain a modified polyacrylate emulsion; the modified polyacrylate emulsion was electrospun, allowed to stand for 8 hours, and naturally cooled to room temperature to obtain modified polyacrylate fibers.
[0023] Comparative Example 1 A method for preparing high-strength cold-resistant fiber mainly comprises the following preparation steps: (1) Take 7 parts of 4-methylcyclohexanone, 4 parts of olefin mixture, 0.04 parts of azobisisobutyronitrile, 2.5 parts of 7% hydrochloric acid solution and 0.9 parts of dimethyldimethoxysilane by weight, heat 4-methylcyclohexanone to 142°C, add olefin mixture, azobisisobutyronitrile, hydrochloric acid solution and dimethyldimethoxysilane at a uniform rate within 1.5 hours, heat to 150°C, continue to react for 80 minutes, then cool to room temperature, adjust pH to 7 with dimethylethanolamine, and prepare polyacrylate emulsion; (2) Graphene oxide and deionized water were mixed in a mass ratio of 1:90, ultrasonicated for 60 minutes, a carboxyl activator of the same mass as the graphene oxide was added, activated for 30 minutes, taken out, and 1-aminopyrrole of the same mass as the graphene oxide was added at a uniform speed within 9 minutes at 60°C and 250 r / min, and stirring was continued for 90 minutes. The mixture was immersed in ethanol and allowed to stand for 60 minutes, centrifuged, washed with ethanol 4 times, and vacuum dried at -5°C for 24 hours to obtain pre-modified graphene oxide; pre-modified graphene oxide, 1-aminopyrrole, ethanol and deionized water were mixed in a mass ratio of 1:4:2:8, stirred at 250 r / min for 9 minutes, filtered, and dried at 50°C for 24 hours to obtain modified graphene oxide; (3) The modified graphene oxide, 2,5-dihydroxyterephthalaldehyde, polyacrylate emulsion and ethanol were uniformly mixed in a molar ratio of 1:0.85:11:7 to obtain a modified polyacrylate emulsion; the modified polyacrylate emulsion was electrospun, allowed to stand for 7 hours, and naturally cooled to room temperature to obtain modified polyacrylate fibers.
[0024] Comparative Example 2 A method for preparing high-strength cold-resistant fiber mainly comprises the following preparation steps: (1) In an air atmosphere, diphenylphosphine and triallylmethoxysilane were uniformly mixed in a molar ratio of 3:1, placed in a high-pressure reactor, and reacted at 120°C for 11 hours to obtain phosphorus-containing siloxane; at 250 r / min, under nitrogen protection, the phosphorus-containing siloxane solution was uniformly added to a nickel bromide solution of equal mass to the phosphorus-containing siloxane solution within 14 minutes, and the mixture was stirred for 24 hours, and dried at 45°C for 23 hours to obtain a silicon-phosphorus-nickel complex; (2) Take 7 parts of 4-methylcyclohexanone, 4 parts of olefin mixture, 0.04 parts of azobisisobutyronitrile, 2.5 parts of 7% hydrochloric acid solution and 0.9 parts of silicon mixture by mass, heat 4-methylcyclohexanone to 142°C, add olefin mixture, azobisisobutyronitrile, hydrochloric acid solution and silicon mixture at a uniform rate within 1.5 hours, heat to 150°C, continue to react for 80 minutes, then cool to room temperature, adjust pH to 7 with dimethylethanolamine, and prepare polyacrylate emulsion; mix polyacrylate emulsion, sodium sulfide and deionized water in a mass ratio of 1:0.4:1, stir at 250 r / min for 2.5 minutes, take 4-methylcyclohexanone layer, and prepare pre-modified polyacrylate emulsion; (3) Graphene oxide and deionized water were mixed in a mass ratio of 1:90, ultrasonicated for 60 minutes, a carboxyl activator of the same mass as the graphene oxide was added, activated for 30 minutes, taken out, and 1-aminopyrrole of the same mass as the graphene oxide was added at a uniform speed within 9 minutes at 60°C and 250 r / min, and stirring was continued for 90 minutes. The mixture was immersed in ethanol and allowed to stand for 60 minutes, centrifuged, washed with ethanol 4 times, and vacuum dried at -5°C for 24 hours to obtain pre-modified graphene oxide; pre-modified graphene oxide, 1-aminopyrrole, ethanol and deionized water were mixed in a mass ratio of 1:4:2:8, stirred at 250 r / min for 9 minutes, filtered, and dried at 50°C for 24 hours to obtain modified graphene oxide; (4) The modified graphene oxide, 2,5-dihydroxyterephthalaldehyde, pre-modified polyacrylate emulsion and ethanol were uniformly mixed in a molar ratio of 1:0.85:11:7 to obtain a modified polyacrylate emulsion; the modified polyacrylate emulsion was electrospun, allowed to stand for 7 hours, and naturally cooled to room temperature to obtain modified polyacrylate fibers.
[0025] Comparative Example 3 A method for preparing high-strength cold-resistant fiber mainly comprises the following preparation steps: (1) In an air atmosphere, diphenylphosphine and triallylmethoxysilane were uniformly mixed in a molar ratio of 3:1, placed in a high-pressure reactor, and reacted at 120°C for 11 hours to obtain phosphorus-containing siloxane; at 250 r / min, under nitrogen protection, the phosphorus-containing siloxane solution was uniformly added to a nickel bromide solution of equal mass to the phosphorus-containing siloxane solution within 14 minutes, and the mixture was stirred for 24 hours, and dried at 45°C for 23 hours to obtain a silicon-phosphorus-nickel complex; (2) Take 7 parts of 4-methylcyclohexanone, 4 parts of olefin mixture, 0.04 parts of azobisisobutyronitrile and 2.5 parts of 7% hydrochloric acid solution by mass, heat 4-methylcyclohexanone to 142°C, add olefin mixture, azobisisobutyronitrile and hydrochloric acid solution at a uniform rate within 1.5 hours, heat to 150°C, continue to react for 80 minutes, then cool to room temperature, adjust pH to 7 with dimethylethanolamine, and prepare polyacrylate emulsion; mix polyacrylate emulsion, sodium sulfide and deionized water in a mass ratio of 1:0.4:1, stir at 250 r / min for 2.5 minutes, take the 4-methylcyclohexanone layer, add zinc bromide (0.09 times the mass of polyacrylate emulsion), stir at 250 r / min for 3 hours, and prepare pre-modified polyacrylate emulsion; (3) Graphene oxide and deionized water were mixed in a mass ratio of 1:90, ultrasonicated for 60 minutes, a carboxyl activator of the same mass as the graphene oxide was added, activated for 30 minutes, taken out, and 1-aminopyrrole of the same mass as the graphene oxide was added at a uniform speed within 9 minutes at 60°C and 250 r / min, and stirring was continued for 90 minutes. The mixture was immersed in ethanol and allowed to stand for 60 minutes, centrifuged, washed with ethanol 4 times, and vacuum dried at -5°C for 24 hours to obtain pre-modified graphene oxide; pre-modified graphene oxide, 1-aminopyrrole, ethanol and deionized water were mixed in a mass ratio of 1:4:2:8, stirred at 250 r / min for 9 minutes, filtered, and dried at 50°C for 24 hours to obtain modified graphene oxide; (4) The modified graphene oxide, 2,5-dihydroxyterephthalaldehyde, pre-modified polyacrylate emulsion and ethanol were uniformly mixed in a molar ratio of 1:0.85:11:7 to obtain a modified polyacrylate emulsion; the modified polyacrylate emulsion was electrospun, allowed to stand for 7 hours, and naturally cooled to room temperature to obtain modified polyacrylate fibers.
[0026] Comparative Example 4 A method for preparing high-strength cold-resistant fiber mainly comprises the following preparation steps: (1) In an air atmosphere, diphenylphosphine and triallylmethoxysilane were uniformly mixed in a molar ratio of 3:1, placed in a high-pressure reactor, and reacted at 120°C for 11 hours to obtain phosphorus-containing siloxane; at 250 r / min, under nitrogen protection, the phosphorus-containing siloxane solution was uniformly added to a nickel bromide solution of equal mass to the phosphorus-containing siloxane solution within 14 minutes, and the mixture was stirred for 24 hours, and dried at 45°C for 23 hours to obtain a silicon-phosphorus-nickel complex; (2) Take 7 parts of 4-methylcyclohexanone, 4 parts of olefin mixture, 0.04 parts of azobisisobutyronitrile, 2.5 parts of 7% hydrochloric acid solution and 0.9 parts of silicon mixture by mass, heat 4-methylcyclohexanone to 142°C, add olefin mixture, azobisisobutyronitrile, hydrochloric acid solution and silicon mixture at a uniform rate within 1.5 hours, heat to 150°C, continue to react for 80 minutes, then cool to room temperature, adjust pH to 7 with dimethylethanolamine, and prepare polyacrylate emulsion; mix polyacrylate emulsion, sodium sulfide and deionized water in a mass ratio of 1:0.4:1, stir at 250 r / min for 2.5 minutes, take the 4-methylcyclohexanone layer, add zinc bromide (0.09 times the mass of polyacrylate emulsion), stir at 250 r / min for 3 hours, and prepare pre-modified polyacrylate emulsion; (3) Graphene oxide, 2,5-dihydroxyterephthalaldehyde, pre-modified polyacrylate emulsion and ethanol were uniformly mixed in a molar ratio of 1:0.85:11:7 to obtain a modified polyacrylate emulsion; the modified polyacrylate emulsion was electrospun, allowed to stand for 7 hours, and naturally cooled to room temperature to obtain modified polyacrylate fibers.
[0027] Comparative Example 5 A method for preparing high-strength cold-resistant fiber mainly comprises the following preparation steps: (1) In an air atmosphere, diphenylphosphine and triallylmethoxysilane were uniformly mixed in a molar ratio of 3:1, placed in a high-pressure reactor, and reacted at 120°C for 11 hours to obtain phosphorus-containing siloxane; at 250 r / min, under nitrogen protection, the phosphorus-containing siloxane solution was uniformly added to a nickel bromide solution of equal mass to the phosphorus-containing siloxane solution within 14 minutes, and the mixture was stirred for 24 hours, and dried at 45°C for 23 hours to obtain a silicon-phosphorus-nickel complex; (2) Take 7 parts of 4-methylcyclohexanone, 4 parts of olefin mixture, 0.04 parts of azobisisobutyronitrile, 2.5 parts of 7% hydrochloric acid solution and 0.9 parts of silicon mixture by mass, heat 4-methylcyclohexanone to 142°C, add olefin mixture, azobisisobutyronitrile, hydrochloric acid solution and silicon mixture at a uniform rate within 1.5 hours, heat to 150°C, continue to react for 80 minutes, then cool to room temperature, adjust pH to 7 with dimethylethanolamine, and prepare polyacrylate emulsion; mix polyacrylate emulsion, sodium sulfide and deionized water in a mass ratio of 1:0.4:1, stir at 250 r / min for 2.5 minutes, take the 4-methylcyclohexanone layer, add zinc bromide (0.09 times the mass of polyacrylate emulsion), stir at 250 r / min for 3 hours, and prepare pre-modified polyacrylate emulsion; (3) Graphene oxide and deionized water were mixed in a mass ratio of 1:90, ultrasonicated for 60 minutes, a carboxyl activator of the same mass as the graphene oxide was added, activated for 30 minutes, taken out, and 1-aminopyrrole of the same mass as the graphene oxide was added at a uniform speed within 9 minutes at 60°C and 250 r / min, and stirring was continued for 90 minutes. The mixture was immersed in ethanol and allowed to stand for 60 minutes, centrifuged, washed with ethanol 4 times, and vacuum dried at -5°C for 24 hours to obtain pre-modified graphene oxide; pre-modified graphene oxide, 1-aminopyrrole, ethanol and deionized water were mixed in a mass ratio of 1:4:2:8, stirred at 250 r / min for 9 minutes, filtered, and dried at 50°C for 24 hours to obtain modified graphene oxide; (4) The modified graphene oxide, the pre-modified polyacrylate emulsion and ethanol were uniformly mixed in a molar ratio of 1:11:7 to obtain a modified polyacrylate emulsion; the modified polyacrylate emulsion was electrospun, allowed to stand for 7 hours, and naturally cooled to room temperature to obtain modified polyacrylate fibers.
[0028] Comparative Example 6 A method for preparing high-strength cold-resistant fiber mainly comprises the following preparation steps: (1) In an air atmosphere, diphenylphosphine and triallylmethoxysilane were uniformly mixed in a molar ratio of 3:1, placed in a high-pressure reactor, and reacted at 120°C for 11 hours to obtain phosphorus-containing siloxane; at 250 r / min, under nitrogen protection, the phosphorus-containing siloxane solution was uniformly added to a nickel bromide solution of equal mass to the phosphorus-containing siloxane solution within 14 minutes, and the mixture was stirred for 24 hours, and dried at 45°C for 23 hours to obtain a silicon-phosphorus-nickel complex; (2) Take 7 parts of 4-methylcyclohexanone, 4 parts of olefin mixture, 0.04 parts of azobisisobutyronitrile, 2.5 parts of 7% hydrochloric acid solution and 0.9 parts of silicon mixture by mass, heat 4-methylcyclohexanone to 142°C, add olefin mixture, azobisisobutyronitrile, hydrochloric acid solution and silicon mixture at a uniform rate within 1.5 hours, heat to 150°C, continue to react for 80 minutes, then cool to room temperature, adjust pH to 7 with dimethylethanolamine, and prepare polyacrylate emulsion; mix polyacrylate emulsion, sodium sulfide and deionized water in a mass ratio of 1:0.4:1, stir at 250 r / min for 2.5 minutes, take the 4-methylcyclohexanone layer, add zinc bromide (0.09 times the mass of polyacrylate emulsion), stir at 250 r / min for 3 hours, and prepare pre-modified polyacrylate emulsion; (3) 2,5-dihydroxyterephthalaldehyde, pre-modified polyacrylate emulsion and ethanol were uniformly mixed in a molar ratio of 0.85:11:7 to obtain a modified polyacrylate emulsion; the modified polyacrylate emulsion was electrospun, allowed to stand for 7 hours, and naturally cooled to room temperature to obtain modified polyacrylate fibers.
[0029] Test Example 1 Flame retardancy test The limiting oxygen index was tested according to GB / T2406 test standard. The results are shown in Table 1.
[0030] Table 1
[0031] From the comparison of the experimental data in Table 1, it can be found that the high-strength cold-resistant fiber prepared by the present invention has good flame retardancy.
[0032] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1 in Table 1, it can be found that the limiting oxygen index of Examples 1, 2, 3 is larger than that of Comparative Example 1, which indicates that the organic phosphorus in the silicon-phosphorus-nickel complex can react chemically with the active free radicals generated during the combustion process, thereby inhibiting the generation and conduction of free radicals and preventing the effective contact between oxygen and the combustion material, which can reduce the activity of the surface of the combustion material, slow down the formation of flames and the rate of combustion reaction, thereby playing a flame retardant role. At the same time, the organic phosphorus can also release a large amount of phosphorus-containing compounds during the combustion process. These compounds can generate phosphates with carbon on the surface of the combustion material at high temperature to form a phosphate protective layer, which covers the surface of the combustion material and plays a role of heat insulation and oxygen isolation, preventing the combustion material from continuing to burn, thereby improving the flame retardant ability of the material and increasing the limiting oxygen index of the material; From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3, it can be found that the limiting oxygen index of Examples 1, 2, 3 is larger than that of Comparative Example 3, which indicates that when the silicon-oxygen long chain burns, the silicon-oxygen bond in the molecule will be converted into a silicon-carbon bond, and together with the generated carbonized product, a composite carbon layer is formed. This composite carbon layer has the advantages of blocking heat, isolating oxygen, and preventing molten droplets, and seals the polymer material to prevent the combustible gas from diffusing outward, thereby improving the flame retardancy of the material and increasing the limiting oxygen index of the material; From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4, it can be found that the limiting oxygen index of Examples 1, 2, 3 is larger than that of Comparative Example 4, which shows that polypyrrole decomposes to produce non-combustible gas after absorbing heat, which can dilute the concentration of oxygen in the air and combustibles produced by thermal decomposition of the polymer on the one hand, and the nitrogen oxides produced by the decomposition can capture free radicals on the other hand, inhibiting the chain reaction of the polymer, thereby improving the flame retardancy of the material.
[0033] Test Example 2 Strength and anti-aging tests Strength test: YG061F electronic single yarn strength tester is used to test the fiber tensile breaking strength, and the test standard is GB / T14344; Anti-aging test: The artificial accelerated light aging test was carried out according to ISO4892-3 international standard, using fluorescent ultraviolet lamp UV-A340. After 15 days of irradiation, the fiber tensile strength was tested using a YG061F electronic single yarn strength tester. The test standard was GB / T14344, and the tensile fracture retention rate was calculated, where the tensile fracture retention rate = tensile fracture strength after aging treatment / tensile fracture strength before aging treatment * 100%. The results are shown in Table 2.
[0034] Table 2
[0035] From the comparison of the experimental data in Table 2, it can be found that the high-strength cold-resistant fiber prepared by the present invention has high strength and good anti-aging ability.
[0036] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3 in Table 2, it can be found that the tensile fracture strength of Examples 1, 2, 3 is greater than that of Comparative Example 3, which shows that the long chain of polysiloxane can enhance the mechanical properties of the material and increase the tensile fracture strength of the material; From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 5, it can be found that the fracture retention rates of Examples 1, 2, 3 are greater than those of Comparative Example 5, which indicates that the surfaces of the modified graphene oxide and the pre-modified polyacrylate emulsion are rich in amino groups that can react with the aldehyde groups of 2,5-dihydroxyterephthalaldehyde, and form a structure that can absorb ultraviolet light with the hydroxyl groups on 2,5-dihydroxyterephthalaldehyde, thereby achieving an anti-aging effect and increasing the fracture retention rate of the material.
[0037] Test Example 3 Antistatic test The surface resistivity of the samples was measured using a surface resistance tester. The results are shown in Table 3.
[0038] Table 3
[0039] From the comparison of the experimental data in Table 3, it can be found that the high-strength cold-resistant fiber prepared by the present invention has good antistatic ability.
[0040] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4 in Table 3, it can be found that the surface resistivity of Examples 1, 2, 3 is lower than that of Comparative Example 4, which shows that polypyrrole is a conductive polymer that can absorb and disperse static charges, thereby reducing the accumulation of static electricity and lowering the surface resistivity of the material.
[0041] Test Example 4 Antimicrobial testing The fiber was tested according to the GB / T20944 oscillation method, where the selected bacteria were Staphylococcus aureus and Escherichia coli. The results are shown in Table 4.
[0042] Table 4
[0043] From the comparison of the experimental data in Table 4, it can be found that the bio-based antibacterial fiber prepared in the present invention has good antibacterial ability.
[0044] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1 in Table 4, it can be found that the antibacterial rates of Examples 1, 2, 3 are higher than those of Comparative Example 1, which shows that zinc ions can destroy their biofilm and metabolic basis, and can also affect the DNA replication and transcription of bacteria, hinder their growth and reproduction, achieve the effect of inhibiting and killing bacteria, and improve the antibacterial rate of the material.
[0045] Test Example 5 Cold test Thermal insulation coefficient test: The fiber is woven into fabric, and the heat dissipation is tested with a YG606 flat-plate thermal insulation instrument to calculate the thermal insulation rate, where thermal insulation rate = (heat dissipation without sample - heat dissipation with sample) / heat dissipation without sample * 100%. The results are shown in Table 5.
[0046] Table 5
[0047] From the comparison of the experimental data in Table 5, it can be found that the bio-based antibacterial fiber prepared by the present invention has good cold-proof performance.
[0048] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 6 in Table 5, it can be found that the antibacterial rates of Examples 1, 2, 3 are higher than those of Comparative Example 6, which shows that graphene oxide has good thermal conductivity and can effectively conduct the heat generated by the human body to various parts of the fiber, keeping the body temperature evenly distributed, improving the warming effect, and effectively preventing the invasion of cold air from the outside, reducing heat loss, thereby enhancing the warming effect and increasing the thermal insulation rate of the material. The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A high-strength cold-resistant fiber, characterized in that: The high-strength cold-resistant fiber is prepared by electrostatic spinning after the modified graphene oxide, 2,5-dihydroxyterephthalaldehyde and pre-modified polyacrylate emulsion react; The modified graphene oxide is prepared by batch reaction of graphene oxide and 1-aminopyrrole; The pre-modified polyacrylate emulsion is prepared by reacting an olefin mixed solution, azobisisobutyronitrile, a hydrochloric acid solution and a silicon mixed solution, diluting the mixture with 4-methylcyclohexanone, and then reacting the mixture with zinc bromide.
2. A method for preparing high-strength cold-resistant fiber, characterized in that: The preparation method of the high-strength cold-resistant fiber mainly includes the following preparation steps: (1) In an air atmosphere, diphenylphosphine and triallylmethoxysilane are uniformly mixed in a molar ratio of 3:1, placed in a high-pressure reactor, and reacted at 115-125°C for 10-12 hours to obtain phosphorus-containing siloxane; at 200-300 r / min, under nitrogen protection, the phosphorus-containing siloxane solution is uniformly added to a nickel bromide solution of equal mass to the phosphorus-containing siloxane solution within 10-18 minutes, and the stirring is continued for 22-26 hours, and the mixture is dried at 40-50°C for 22-24 hours to obtain a silicon-phosphorus-nickel complex; (2) Take 6-8 parts of 4-methylcyclohexanone, 3-5 parts of olefin mixture, 0.03-0.05 parts of azobisisobutyronitrile, 2-3 parts of 6-8% hydrochloric acid solution and 0.8-1 parts of silicon mixture by mass, heat 4-methylcyclohexanone to 140-144°C, add olefin mixture, azobisisobutyronitrile, hydrochloric acid solution and silicon mixture at a uniform rate within 1-2 hours, heat to 145-155°C, continue reaction for 70-90 minutes, and then reduce to room temperature. The mixture was heated to room temperature, and the pH was adjusted to 6.5-7.5 with dimethylethanolamine to obtain a polyacrylate emulsion; the polyacrylate emulsion, sodium sulfide and deionized water were mixed in a mass ratio of 1:0.3-0.5:1, and stirred at 200-300 r / min for 2-3 min, a 4-methylcyclohexanone layer was taken, and zinc bromide in an amount of 0.08-0.1 times the mass of the polyacrylate emulsion was added, and stirred at 200-300 r / min for 2-4 h to obtain a pre-modified polyacrylate emulsion; (3) Mix graphene oxide and deionized water in a mass ratio of 1:80~100, ultrasonicate for 50~70min, add a carboxyl activator of the same mass as graphene oxide, activate for 25~35min, take out, add 1-aminopyrrole of the same mass as graphene oxide at a uniform speed within 8~10min at 50~70℃ and 200~300r / min, continue stirring for 80~100min, immerse in ethanol and let stand for 50~70min, centrifuge, wash with ethanol 3~5 times, and vacuum dry at -10~0℃ for 22~26h to obtain pre-modified graphene oxide; mix pre-modified graphene oxide, 1-aminopyrrole, ethanol and deionized water in a mass ratio of 1:3~5:1~3:7~9, stir at 200~300r / min for 8~10min, filter, and dry at 40~60℃ for 22~26h to obtain modified graphene oxide; (4) The modified graphene oxide, 2,5-dihydroxyterephthalaldehyde, pre-modified polyacrylate emulsion and ethanol are uniformly mixed in a molar ratio of 1:0.8-0.9:10-12:6-8 to obtain a modified polyacrylate emulsion; the modified polyacrylate emulsion is electrospun, allowed to stand for 6-8 hours, and naturally cooled to room temperature to obtain modified polyacrylate fibers.
3. The method for preparing a high-strength cold-resistant fiber according to claim 2, characterized in that: The phosphorus-containing siloxane solution in step (1) is prepared by uniformly mixing phosphorus-containing siloxane and dichloromethane in a mass ratio of 1:4-5.
4. The method for preparing a high-strength cold-resistant fiber according to claim 2, characterized in that: The nickel bromide solution in step (1) is prepared by uniformly mixing nickel bromide and dichloromethane in a mass ratio of 1:8-10.
5. The method for preparing high-strength cold-resistant fiber according to claim 2, characterized in that: The olefin mixed liquid in step (2) is prepared by uniformly mixing methyl methacrylate, isooctyl acrylate, butyl acrylate, allyltrimethoxysilane and acrylamine in a mass ratio of 1:1:1:0.3-0.5:0.3-0.
5.
6. The method for preparing a high-strength cold-resistant fiber according to claim 2, characterized in that: The silicon mixed solution in step (2) is prepared by uniformly mixing dimethyldimethoxysilane and silicon-phosphorus-nickel complex in a mass ratio of 1:0.2-0.
4.
7. The method for preparing high-strength cold-resistant fiber according to claim 2, characterized in that: The carboxyl activator in step (3) is prepared by uniformly mixing 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide in a mass ratio of 1:
1.
8. The method for preparing high-strength cold-resistant fiber according to claim 2, characterized in that: The electrospinning parameters of step (4) are as follows: liquid flow rate of 0.18-0.22 ml / h, receiving distance of 14-16 cm, and spinning voltage of 16-18 KV.
Citation Information
Patent Citations
Energy absorbing method based on dynamic cross-linking polymer
CN109666162A
Combined energy absorption method and application thereof
CN111378168A
Multi-layer structure assembly with force-induced responsiveness
CN113997650A
Dustproof corrosion-resistant fabric and preparation method thereof
CN116815496A
Soft hollow warm-keeping fiber fabric and preparation method thereof
CN118273130A
Cited By
High-weather-resistance photovoltaic panel coating material and preparation method thereof
CN120365778A
Acid and alkali resistant and salt spray resistant coating and preparation method thereof
CN120365850A
High-temperature-resistant and low-temperature-resistant plastic film and preparation method thereof
CN120484480A
